An investigation on the impact of loan words in the teaching of isindebele in Khami district Bulawayo province. - Ndlovu, Busweswe (Midlands State University, 2017)
Schools in Khami District have not been spared from the influence of loan words in the teaching of the Ndebele language. The researcher focused on the impact of loan words in the teaching of Ndebele language in the selected Khami District Schools of Bulawayo Province .The Schools were Dumezweni Primary School, Godlwayo Primary School and Ngwalongwalo Primary School. The target population comprised of the heads of the schools , teachers and grade 7 pupils in selected Khami District Schools .The study adopted a descriptive research design and used a mixed method approach in which questionnaires were comprising of open and close ended questions .The questionnaires were administered to teachers and students whereas interview guides were administered to the heads of Schools .The questionnaire and the interview guides were administered to 15 teachers and 18 students who were selected using a stratified random sampling method . The sample was drawn from a population of 50 (30 students were grade 7 pupils from the selected 3 schools and 20 were teachers from those selected schools) and 3 heads of schools were given interview guides since they were the heads of those selected schools. The results were presented in tables, pie charts, narrations, codes and themes. The need for the Government to enactment the policies that encourage the use of proper Ndebele vocabulary was of a great interest to the respondents. Data was gathered from both primary and secondary sources .Research findings also revealed that the main problem presented by loan words to the Ndebele language was the erosion of the Ndebele language, loan words were accepted in the Zimbabwean education system. In light of these findings , the study recommended that there should be clear language policy that supports the use and teaching of indigenous languages that would encourage proper use of native languages .The research also recommends that the Government should come up with the policies and Educational curriculum that supports the use of indigenous languages .The research further recommends that the Examination boards like ZIMSEC should set Ndebele questions in proper Ndebele language so that learners can use the correct Ndebele vocabulary .Therefore the markers should penalize the students who do not answer Ndebele questions in proper Ndebele language. Further study should be carried out on the effectiveness of strategies in place to solve the influence of other languages on the Ndebele language.